La educación como acogida: una propuesta desde la ética de Levinas - Ortega Ruiz, Pedro; Romero Sánchez, Eduardo (Pontificia Universidad Católica del Perú, 2024)
Emmanuel Levinas, one of the most profoundly original western philosophers of the 20th Century, has attracted considerable attention in recent years amongst educators and philosophers of education. His thought has several ethical implications for education in areas related with moral education, diversity issues, multiculturalism, or recognition policies. This paper is based on Levinas’ claim that the concept of responsibility builds the cornerstone of his philosophical work, and that responsibility is most clearly manifested in the welcoming of the other. To educate is to welcome, to accompany and to help the pupil in its life plan. According to Levinas’ ethics, welcoming is not understood as a mere object of instruction or teaching: “learning” takes place through contagion, through mimesis. Therefore, the paper criticizes an approach that stresses previously programmed concrete teaching activities, and defends the need to create a teaching environment in the classroom that encourages openness to the other, especially to those who are culturally different. It concludes showing the importance of a welcoming teaching that explores the feeling of responsibility and takes the experience of the pupil as the starting point of teaching action.

Emmanuel Levinas, uno de los filósofos occidentales más profundamente originales del siglo XX, ha recibido en los últimos años una atención considerable por parte de educadores y filósofos de la educación. Son muchas las implicaciones éticas que tiene para la educación en áreas relacionadas con la educación moral, cuestiones de diversidad, multiculturalismo y políticas de reconocimiento. Este artículo se apoya en Levinas para quien el concepto de responsabilidad constituye la piedra angular de su obra filosófica y encuentra su mejor expresión en la acogida al otro. Educar es acoger, acompañar y ayudar al educando en su proyecto de vida. Desde la ética levinasiana, la acogida no se concibe como un mero objeto de instrucción o de enseñanza, se “aprende” por contagio, por mimesis. Por ello, los autores se muestran contrarios a la propuesta de actuaciones educativas concretas previamente programadas, y apuestan por la creación de un clima educativo en el aula que favorezca la apertura al otro, especialmente al diferente cultural. Concluyen en la importancia de una educación hospitalaria que profundice en el sentido de la responsabilidad y haga de la experiencia del alumno el punto de partida de la acción educativa.
Education as Welcoming: A Proposal based on Levinas’ Ethics
Keywords: Education; Ethics; Welcoming; Alterity; Different culture; Educación; Ética; Acogida; Alteridad; Diferente cultura; https://purl.org/pe-repo/ocde/ford#6.03.01